Tracking users mobility patterns towards CO2 footprint - Ferreira, J. C.; Monteiro, V.; Afonso, J. A.; Afonso, J. L. (Distributed Computing and Artificial Intelligence, 13th International Conference. Advances in Intelligent Systems and Computing, 2016)
This research work is based on the development of a mobile application and associated central services for tracking users’ movements in a city, identifying the transportation mode and routes performed. This passive tracking generates useful data about users’ habits, which are then associated with the CO2 emission in the form of a mobility invoice, with the goal of enabling the users to understand their carbon footprint resulting from the users’ mobility process in the city. The performance of the developed system is validated through experimental tests based on data collected during six months from more than 2500 mobility experiences.